Feasibility and safety of bowel cleansing using low‐volume polyethylene glycol with ascorbic acid before pediatric colonoscopy: A pilot study. Issue 2 (16th November 2016) - Tsunoda, Tomoyuki; Sogo, Tsuyoshi; Iwasawa, Kentaro; Umetsu, Shuichiro; Oikawa‐Kawamoto, Manari; Inui, Ayano; Fujisawa, Tomoo
Abstract : Background and Aim: To assess the feasibility and safety of same‐day regimen of low‐volume polyethylene glycol solution with ascorbic acid for bowel cleansing before colonoscopy in children. Methods: Data on children who received polyethylene glycol solution with ascorbic acid for bowel cleansing in our department were retrospectively analyzed. On the day before the procedure, patients ate a low‐residue diet and received sodium picosulfate in the evening. The following day, patients took polyethylene glycol solution with ascorbic acid in the morning; the procedure was carried out in the afternoon. Dosages of sodium picosulfate and polyethylene glycol solution with ascorbic acid were adjusted based on bodyweight. Bowel cleansing efficacy was rated on a scale of 1–5 by the colonoscopist. Results: Between July 2013 and November 2014, polyethylene glycol solution with ascorbic acid was used in 112 cases (96 patients; male : female 73:39; median age 10.9 years, range 4–19 years). Ninety‐one cases (81%) were able to orally ingest the prescribed amount of polyethylene glycol solution with ascorbic acid. Satisfactory bowel cleansing (cleansing grade ≥3) was attained in 87% on intention‐to‐treat analysis and 85% on per‐protocol analysis. Cleansing grade was significantly better in children who ingested polyethylene glycol solution with ascorbic acid within 60 min ( P < 0.05). There were no serious adverse events. Conclusion: Same‐day regimen of polyethylene glycol solution with ascorbic acid is effective and safe for bowel cleansing in children.